THE ANTAGONISM BETWEEN ACETIC ACID AND THE CHLORIDES OF SODIUM, POTASSIUM, AND CALCIUM AS MANIFESTED IN DEVELOPING FUNDULUS EMBRYOS - Armstrong, Philip B. (The Rockefeller University Press, 1928)
1. Developing Fundulus embryos react in much the same way to mixtures of acetic acid in salt solutions whether their membranes are removed or not. It is therefore not necessary to assume any specific rôle for the membrane. 2. The primary toxic effect of acetic acid is to kill the surface of the embryo; heart stoppage is due to penetration of the acid after the surface has been injured. 3. The salt (NaCl, KCl, CaCl(2)) antagonizes the acetic acid by slowing or preventing the killing of the surface of the embryo. 4. If embryos are immersed in certain KCl-acetic acid mixtures, the surface killing effect of the acid is antagonized but at the same time the KCl penetrates and stops the heart in the manner which is characteristic of a KCl solution alone.